ETHNOMATHEMATICS-BASED LEARNING DESIGN OF MOUNTAINOUS PAPUA TO INCREASE STUDENT ENGAGEMENT AND CREATE MEANINGFUL LEARNING - Sabon, Yuliana Olga Siba; Telussa, Rivaldo Paul (Jurnal Pendidikan Matematika (JUPITEK), 2024)
The application of ethnomathematics in teaching has many benefits. Cultural diversity can be an interactive learning resource for students. One culture that has high ethnomathematics potential is the Papuan Mountain culture. Although several examples of ethnomathematics have been found in Papuan culture, the design of ethnomathematics applications in learning is still very minimal. In addition, the lack of student involvement in the ethnomathematics exploration process is an important reason for the need to develop ethnomathematics-based learning based on 21st-century learning. The type of research is research development by using the nine stages of Dick and Carey’s development. The results of research and development concluded that the mountain ethnomathematics-based learning design was developed in 4 main stages, namely analysis, development design, implementation, and evaluation. Strategies that can be used in ethnomathematics-based learning in Papua Mountains to increase learner involvement and create meaningful learning are exploration, oriented to problem statements, constructing knowledge and experiences of learners based on their culture. The results of the analysis show that the ethnomathematics-based learning design of the culture of the Papua Mountains is good and feasible to implement with a validity index of 0.802 while the reliability index of rater agreement on the learning design is good, namely 0.896.